Preparation of an Antimicrobial and Antioxidant Bio-Polymer Film and Its Application as Glazing Shell for Postharvest Quality of Fresh-Cut Apple - Zhaohui Yang; Yalan Zhang; Yihui Zhao; Hao Dong; Jian Peng; Qi He (Foods, 2022)
The aim of this work is to glazing a modified bio-polymer shell as substitute of peel to keep the postharvest quality of fresh-cut fruits. In this study, chitosan as backbone of the shell was modified by addition of the functional extracts obtained from Zanthoxylum, in which 12 kinds of main identified bio-active components consisted of over 55% of the total extracts. The introduction of the extracts improved physic and mechanical properties of the shell, and endowed it with significant antimicrobial and antioxidant activity. Accordingly, the modified chitosan was used as the substitute of peel to preserve fresh-cut apples. Results exhibited that such treatments obviously delayed the decline process of overall postharvest quality of the preserved apple samples throughout all the storage period, represented by the variations in physical, chemical, and microbial properties of the apple samples were significantly inhibited. The overall observations revealed promising potential of the bio-polymer shell in food application.